Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages clearly desirable, and there should also be some safeguard for the conscientious doctor against victimization by a bad management. Medical men are not well trained for industry. As students they hardly get any training at all on factory health dangers, and it is up to the workers to help any newly appointed medical men in this respect. It may be difficult in certain instances to achieve, but one object of any works' committee that is seriously tackling health problems should be co-operation with the doctor or nurse on the staff. If properly approached, they are likely to be only too grateful for the mass of information that only the workers can give them, while if the workers submit the health problems that arise on account of their work, they will begin to have some measure of control over the work of the medical department. What a Health Department Can Do This is not the place to outline the work it is desirable that a medical department in a factory should carry put, but it may be as well to point out that for proper scientific team work in the fight to maintain health and prevent illness, the technical training of a doctor will be useful. It is all very well to say a doctor cannot even cure a cold, but he can teach what is known about preventing the spread of colds and 'flu, and this is the type of illness that causes most lost time in industry. Because it is mild it is not necessarily unimportant from the production angle. Actually it is of very great importance. If there was an epidemic of some deadly disease like typhus or 'flu of the 1918 type which at one time was killing 80,000 people a week in England, all manner of drastic measures would be taken to stop the spread of infection from one person to another. It is worth while consulting medical opinion as to whether some of these measures might not be taken to combat milder epidemics. Medical men are especially useful in the early detection of actual disease, and in training supervisors or charge-hands to recognize it also. It may be important, for example, where there is a risk of dermatitis in some process, that every one should be inspected superficially daily, but it might be impracticable or wasteful to use a doctor for this inspection. Early detection of all dermatitis cases is a tremendous help in establishing quick cures. This value of early detection applies to all illnesses, ranging from the mild skin inflammation to the deadly skin cancers or from the small clean scratch to the cut that has gone thoroughly septic and 33 21/2049